Immunotherapy and Immune Checkpoints: Unlocking The Immune System’s Potential to Treat Cancer - Rizqoh, Debie; Febrina, Olivia Putri; Pratiwi, Ulfa Hanum; Ramadhani, Abdah Zhafirah; Athalia , Nabila Wine (Fakultas Kedokteran, Universitas Palangka Raya, 2025)
Conventional cancer therapies, such as surgery, chemotherapy, and radiation therapy, often produce limited results and negatively affect patients' quality of life. In recent years, immunotherapy based on immune checkpoint inhibitors (ICIs) has emerged as a promising new approach. Immune checkpoint molecules, such as PD-1, PD-L1, and CTLA-4, play a crucial role in suppressing the immune response to tumors, making them primary targets in ICI therapy. This study examines the mechanisms of immune checkpoints, the efficacy of ICI therapy, and the remaining challenges in clinical practice. The review was conducted through a literature review of scientific publications and the latest clinical trial results. The results demonstrate the efficacy of ICIs, such as ipilimumab and pembrolizumab, in improving overall and progression-free survival rates across various types of cancer, particularly melanoma and non-small cell lung cancer. Combining two ICIs has been shown to have higher synergistic effects than monotherapy, as demonstrated in the CheckMate 067 and KEYNOTE-024 clinical trials. Despite its promise, this therapy is not fully effective in all patients due to immune resistance, autoimmune side effects, and the complexity of tumor heterogeneity and the immune microenvironment. Therefore, combination therapy strategies, dose adjustments, schedule modifications, and personalized approaches based on biomarkers are needed to optimize clinical benefits and expand the scope of therapy. In conclusion, ICIs hold great potential for future cancer therapies and are being developed to be more effective and personalized.